Ketersediaan Ruang Laktasi di Pusat Perbelanjaan Modern Central Park Mall Jakarta Sebagai Wujud Pemenuhan Hak Anak Atas Asi Eksklusif Berdasarkan Permenkes RI Nomor 15 Tahun 2013 Tentang Tata Cara Penyediaan Fasilitas Khusus Menyusui dan/atau Memerah Asi - Riezky Dihita Riani; Nurikah Nurikah; E Rahmat Jazuli (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
Shopping centers as one of the categories of public facilities have the responsibility to support the exclusive breastfeeding program launched by the government. One form of this support is by providing lactation room facilities. Therefore, this study will discuss about how the availability of lactation space in the modern shopping center, Central Park Mall Jakarta, based on Regulation of The Minister of Health Number 15 of 2013 Concerning Procedures for Providing Special Facilities for Breastfeeding and/or Expressing Breastmilk?, How are the efforts of the management of the modern shopping center, Central Park Mall Jakarta in meeting the availability of lactation rooms?. The research method tah the author uses in the preparation of this legal writing is empirical juridicial research, with analytical descriptive spesifications that discuss the implementation of The Minister of Health Number 15 of 2013 Concerning Procedures for Providing Special Facilities for Breasrfeeding and/or Expressing Breastmilk. This study uses primary data sourced from the field in the form of interviews with mall managers, secondary data sourced from laws regulation, official documents, and books which were analyzed qualitatively. Based on the results of the study, the Central Park Mall Jakarta Modern Shopping Center has provided lactation rooms divided into a room per floor, and all room facilities have met the standars set out in the Regulation of Minister of Health Number 15 of 2013 Concerning Procedures for Providing Special Facilities for Breastfeeding and/or Expressing Breastmilk. The efforts made by the manager of Central Park Mall Jakarta in the procurement of lactation rooms are divided into 3 elements, namely mall management, human resources, and facilities and infrastructure.